2013
DOI: 10.5812/jjm.7178
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of AmpC and Extended-Spectrum β-lactamases in Metallo-β-Lactamase Producing Pseudomonas aeruginosa Burn Isolates in Tehran

Abstract: Background: Multi-drug resistant Pseudomonas aeruginosa causes serious complications in burn patients. One of the most important mechanisms of resistance to β-lactam antibiotics is hydrolysis of antibiotics by various β-lactamases. In recent years, Carbapenems have been widely used for treatment of P. aeruginosa infections. However, the organisms have become resistant to Carbapenems mostly by producing metallo β-lactamases. Objectives: The aim of this study was to determine antibiotic susceptibility, productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…However, resistance to the inhibitor indicates the possible presence of AmpC or other consistent enzymes (18). Several previous studies that aimed to detect ESBLs have demonstrated a high level of resistance among P. aeruginosa isolates to antibiotics (19). In this study, more than half of the wound ESBL positive isolates could amplify bla VEB-1 (47%).…”
Section: Discussionmentioning
confidence: 99%
“…However, resistance to the inhibitor indicates the possible presence of AmpC or other consistent enzymes (18). Several previous studies that aimed to detect ESBLs have demonstrated a high level of resistance among P. aeruginosa isolates to antibiotics (19). In this study, more than half of the wound ESBL positive isolates could amplify bla VEB-1 (47%).…”
Section: Discussionmentioning
confidence: 99%
“…Fifty one non-duplicate P. aeruginosa isolates were randomly selected from a collection of burn isolates provided by Shahid Motahari Hospital in 2011. The antibiotic susceptibility patterns and MBL production were previously determined using disc diffusion and the double disc synergy tests, respectively ( 12 ). The isolates were maintained in brain heart infusion broth (Oxoid, UK) containing 10% dimethyl sulfoxide and stored at -20ºC until use.…”
Section: Methodsmentioning
confidence: 99%
“…The antibiotic susceptibility and MBL production of the isolates were determined by disk diffusion and the double disk synergy test (DDS), as previously reported in the literature (10). The organisms were stored at -20 °C in a brain heart infusion broth (Oxoid, UK) containing 10% dimethyl sulfoxide until use.…”
Section: Bacterial Isolatesmentioning
confidence: 99%